2017
DOI: 10.5296/ajfa.v9i2.11761
|View full text |Cite
|
Sign up to set email alerts
|

Debt Capital and Financial Performance: A Comparative Analysis of South African and Sri Lankan Listed Companies

Abstract: This study compares how the debt capital of the listed companies operating in the wholesale and retail sectors of South Africa and Sri Lanka affect their financial performance. Objective of this study is to examine whether debt capital affects the financial performance of the wholesale and retail sector companies in South Africa and Sri Lanka. To examine the impact of debt financing on financial performance of companies over the 2011-2015 period. Fixed-effects (within) regression model was used.The findings th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Further, H3 was also not supported with the results of the study that there was no significant relationship between short term debt to total assets ratio and ROE. Findings of the study were consistent with the studies of Velnampy and Niresh (2012); Ramadan and Ramadan (2015); Siddik et al (2017) and Abewardhana and Magoro (2017).…”
Section: Relationship Between Capital Structure and Roesupporting
confidence: 82%
See 1 more Smart Citation
“…Further, H3 was also not supported with the results of the study that there was no significant relationship between short term debt to total assets ratio and ROE. Findings of the study were consistent with the studies of Velnampy and Niresh (2012); Ramadan and Ramadan (2015); Siddik et al (2017) and Abewardhana and Magoro (2017).…”
Section: Relationship Between Capital Structure and Roesupporting
confidence: 82%
“…Lingesiya and Premkanth (2012) Recently, Abewardhana and Magoro (2017) completed a study on debt capital and financial performance which was a comparative analysis of South African and Sri Lankan listed companies. Their findings of the study were, in case of Sri Lanka, debt financing in terms of short term debt had a negative impact on firm performance while long term debt had a positive impact.…”
Section: The Relationship Between Capital Structure and Financial Permentioning
confidence: 99%
“…The Modigliani and Miller (1958) theory predicted that under conditions of free markets, investor's uniform access to market information and absence of taxes as well as transaction charges, the capital structure remains immaterial in determining the worth of the firm. This theory was more based on assumptions that there were no bankruptcy costs, no information asymmetry among all the firm stakeholders (Abeywardhana, 2017). The same author argues that individual investors can equally access financial markets, as the firm can enable individual investors to create any leverage that was wanted but not offered or get rid of any leverage that the firm took on but was not wanted.…”
Section: Literature Review Theoretical Reviewmentioning
confidence: 99%
“…Accordingly, a raise in the amount of debt leads to a fall in the weighted average cost of capital of a firm until the firm obtains the debt-equity ratio that maximizes its value. Abeywardhana (2017) posits that the problems of financial distress increase proportionately with the amount of debt, resulting into an optimal capital structure that shows the highest possible tax shield the firm can achieve.…”
Section: Literature Review Theoretical Reviewmentioning
confidence: 99%
“…They have found that there was a positive relationship between debt to total assets and return on capital employed. Recently, Abewardhana and Magoro (2017) completed a study on debt capital and financial performance which was a comparative analysis of South African and Sri Lankan listed companies. Their findings of the study were, in case of Sri Lanka, debt financing in terms of short term debt had a negative impact on firm performance while long term debt had a positive impact.…”
Section: Empirical Studies On the Relationship Between Capital Structmentioning
confidence: 99%